Secondary battery and electric device
By adopting a double-layer design in the negative electrode sheet of the secondary battery, using a high ID/IG ratio active material in the second area of the negative electrode film layer, the problem that secondary batteries in the prior art are difficult to take into account both dynamic performance and cycle life, and the effects of high energy density and long cycle life are achieved.
Patent Information
- Application Number
- CN202311679328.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-07
- Publication Date
- 2025-04-18
AI Technical Summary
Existing secondary batteries have difficulty in improving kinetic performance and often require sacrifice of kinetic performance and service life when improving energy density.
The negative electrode sheet design is adopted, which includes a negative electrode current collector and a negative electrode film layer formed on the surface of the current collector. The negative electrode film layer is divided into two regions, and the ID/IG ratio of the active material in the second region is higher than that of the first region. Through this double-layer design, high energy density is achieved at a lower negative electrode film layer thickness and improves the cyclic stability and kinetic performance of the battery.
It achieves improvement of cycle stability and dynamic performance while taking into account the battery's energy density, and extends the battery's service life.
Smart Images

Figure CN119852536A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a secondary battery and an electrical device. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As the application scope of secondary batteries becomes wider and wider, people have put forward severe challenges to the performance of secondary batteries, such as requiring secondary batteries to take into account various performances such as energy density, dynamic performance and service life. However, the problem faced in the prior art is that when improving the dynamic performance of secondary batteries, it is often difficult to take into account the cycle life of secondary batteries; when improving the energy density of secondary batteries, it is often at the expense of the dynamic performance and service life of secondary batteries. Summary of the invention
[0003] The present application is developed in view of the above-mentioned technical problems, and its purpose is to provide a secondary battery with both long cycle life and high energy density.
[0004] In a first aspect, the present application provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, the negative electrode film layer having a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is recorded as H, the region within a thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the first region of the negative electrode film layer, the region within a thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the second region of the negative electrode film layer, and the I of the active material in the second region is D / I G Greater than the I of the active material in the first region D / I G , I D / I G is the ratio of the D peak intensity to the G peak intensity of the Raman spectrum, I D Indicates that the Raman spectrum is at 1350±100cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±100cm -1 The G peak intensity at .
[0005] Raman spectroscopy I D / I G It can be used to characterize the disorder degree of the surface of the active material. It can be understood that the first region and the second region each include at least one active material.D / I G Greater than the I of the active material in the first region D / I G This does not mean that the I of each active material in the second region D / I G The I of any active material in the first region must be greater than D / I G The I of the active material in the negative electrode sheet located in the second region away from the current collector D / I G Greater than the I of the active material in the first region D / I G , which means that the active material in the second region outside the electrode has a higher average disorder degree than the active material in the first region. In materials with high disorder, active ions are more easily embedded in and extracted from the active material, which can effectively reduce the volume expansion during ion extraction and improve the battery's cycle performance; at the same time, the electrolyte is also more likely to penetrate the active material, thereby improving the battery's kinetic performance. The I of the active material in the first region near the current collector in the negative electrode D / I G The active material has a higher capacity and is easy to be compacted during the cold pressing process, which improves the compaction of the pole piece and achieves a high energy density of the secondary battery. D / I G The single-layer pole piece made of mixed active materials can achieve the same battery energy density at a lower negative electrode film thickness through a double-layer design, further overcoming the problem of too long transmission path and reduced battery dynamics caused by high negative electrode film thickness. Therefore, the secondary battery can improve the battery's cycle stability and dynamic performance while taking into account the battery's energy density.
[0006] In any embodiment of the present application, the I of the active material in the second region D / I G The active material I in the first region D / I G The difference ΔK satisfies: 0<ΔK≤0.4, which can be selected as 0.1≤ΔK≤0.25.
[0007] I of the active material in the second region D / I G The active material I in the first region D / I G The secondary battery with the difference ΔK within the above range can more effectively take into account the cycle stability, dynamic performance and battery capacity of the battery.
[0008] In any embodiment of the present application, the active material in the first region has aD / I G Less than or equal to 0.14, optionally 0.05-0.1; and / or, I of the active material in the second region D / I G Greater than or equal to 0.1, optional range is 0.2-0.35.
[0009] I of the active material in the first region D / I G I of the active material in the second region D / I G In the appropriate range, secondary batteries can better improve the battery's cycle stability and kinetic performance.
[0010] In any embodiment of the present application, the particle size distribution (Dv90-Dv10) / Dv50 of the active material in the second region is greater than the particle size distribution (Dv90-Dv10) / Dv50 of the active material in the first region.
[0011] The active material in the second region of the negative electrode sheet away from the current collector has a larger particle size distribution, which is beneficial to the infiltration of the electrolyte in the negative electrode sheet and improves the kinetic performance; while the active material in the first region close to the current collector has a smaller particle size distribution, which is beneficial to obtaining tightly packed negative electrode active materials and improving the compaction density of the negative electrode sheet. In other words, the negative electrode sheet requires a smaller cold pressing pressure to achieve the same compaction density, thereby reducing the probability of cracking of the active material during the cold pressing process, further improving the integrity of the active material during the processing process, and improving the cycle stability of the battery.
[0012] In any embodiment of the present application, the graphitization degree of the active material in the second region is less than the graphitization degree of the active material in the first region.
[0013] Active materials with low graphitization degree often have larger interlayer spacing, which is conducive to the deintercalation of active ions. The active materials located in the second region of the negative electrode sheet away from the current collector have low graphitization degree, which is beneficial to improving the battery kinetic performance while reducing the volume expansion of the electrode sheet caused by the deintercalation of active ions, and comprehensively improving the cycle stability of the battery.
[0014] In any embodiment of the present application, the proportion of primary particles of the active material in the second region is higher than the proportion of primary particles of the active material in the first region.
[0015] A higher primary particle content in the second region located on the negative electrode plate away from the current collector side is beneficial to improving the particle integrity of the plate during the cold pressing process, reducing the generation of new interfaces, reducing the consumption of active lithium during the cycle process, and further improving the cycle stability of the secondary battery.
[0016] In any embodiment of the present application, the active material in the first region includes a first graphite material, and the first particle body of the first graphite material includes an internal region and a surface region at least partially surrounding the internal region, and the surface region refers to a region extending 30 nm from the surface of the first particle body of the first graphite material to the interior of the particle, and the surface region includes a disordered layer.
[0017] In any embodiment of the present application, the thickness of the disordered layer is 1 nm-20 nm.
[0018] Different from the active material with disordered layer coated on the surface of the graphite particle body, the disordered layer of the first graphite material is a part of the graphite particle body, that is, the disordered layer structure in the surface region of the first graphite material and the other parts of the first graphite material are derived from the same precursor, which makes the disordered layer of the first graphite material have high uniformity and extremely thin thickness. The first graphite material has a disordered layer on the surface and has a low I D / I G .
[0019] The disordered layer mainly includes amorphous carbon. The carbon atoms in the amorphous carbon structure have no regular arrangement, which makes the interaction between its molecules more complicated, resulting in higher strength and hardness than the graphite crystals in the internal area, which reduces the probability of surface damage of graphite particles due to friction between particles and between particles and stirring tanks during slurry preparation, reduces the risk of cracking of negative electrode active material particles and exposing new interfaces during the cold pressing of the pole piece, and keeps the graphite material in a higher degree of integrity during the manufacturing process. Graphite materials with high particle integrity have fewer surface defects and a good interface with the electrolyte, which can effectively reduce the side reactions between the negative electrode and the electrolyte, reduce the loss of active lithium, and improve the cycle stability of the battery. At the same time, the first graphite material will not sacrifice the capacity of the graphite material and the energy density of the battery because of the excessive disorder of its surface layer, and can take into account the energy density of the battery while improving the cycle stability of the battery.
[0020] In any embodiment of the present application, the active material in the second region includes a second graphite material, the second graphite material includes a second particle body and a coating layer at least partially coating the surface of the second particle body, and the coating layer includes amorphous carbon.
[0021] The coating layer on the surface of the second graphite material can greatly increase the surface disorder of the active material in the second region. The highly disordered surface of the second graphite material makes it easier for active ions to be deintercalated and reduces the volume expansion during the deintercalation of active ions, further improving the dynamic performance of the battery.
[0022] In any embodiment of the present application, the powder compaction density of the second graphite material under a pressure of 49000N is 1.60g / cm 3 -1.80g / cm 3 .
[0023] Graphite materials with large surface disorder often have high surface strength and hardness, so they are difficult to compact under pressure and have low powder compaction density. The second graphite material has a high surface disorder while still maintaining a high powder compaction density, which is conducive to increasing the ultimate compaction density of the pole piece, thereby further improving the energy density of the battery.
[0024] In any embodiment of the present application, the specific surface area of the first graphite material is 1.0 m 2 / g-1.8m 2 / g, optional 1.1m 2 / g-1.7m 2 / g.
[0025] The low specific surface area of the first graphite material helps to further reduce the degree of side reactions of the active material and improve the cycle life of the secondary battery.
[0026] In any embodiment of the present application, the volume distribution particle size Dv50 of the first graphite material is 7.0 μm-14.0 μm, and can be optionally 8.0 μm-12.0 μm.
[0027] In any embodiment of the present application, the particle size distribution (Dv90-Dv10) / Dv50 of the first graphite material is 1.0-1.4, and can be optionally 1.1-1.3.
[0028] Controlling the particle size distribution of the first graphite material within the above range is conducive to obtaining tightly packed negative electrode active materials and improving the compaction density of the negative electrode sheet. In other words, the cold pressing pressure required for the negative electrode sheet to achieve the same compaction density is smaller, thereby reducing the probability of cracking of the active material during the cold pressing process, and further improving the integrity of the active material during the processing process; and the small stress inside the first graphite material particles is conducive to maintaining the long-period pore structure of the electrode sheet during the cycle, and the original pore structure of the electrode sheet can be maintained during the cycle, so that the lithium ion lithium insertion path remains unobstructed, while reducing the re-filming of the negative electrode active material during the charging process, improving the dynamic performance and cycle life. Furthermore, the particle size distribution within the above range can also improve the uniformity of lithium insertion between particles, reduce polarization, avoid lithium precipitation caused by uneven current density, and is conducive to achieving long-term cycle stability. In addition, the particle size distribution within the above range is also helpful to improve the processing performance of the electrode sheet, and will not affect the uniformity of slurry stirring due to too many small-sized particles in the first graphite material, which is conducive to improving the uniformity and stability of the quality of the electrode sheet, and helps to achieve long-term cycle stability.
[0029] In any embodiment of the present application, the gram capacity of the first graphite material is 345 mAh / g-355 mAh / g, and can be optionally 347 mAh / g-353 mAh / g.
[0030] The first graphite material with a gram capacity within the above range will not undergo significant lattice expansion during the charge and discharge process due to its high graphitization degree; nor will it be difficult to compact the material due to its low graphitization degree. In order to achieve the same electrode compaction density, a higher cold pressing pressure is required, which will cause cracks during the cold pressing process and generate new interfaces during the cycle process to consume too much active lithium. The above two aspects can comprehensively improve the cycle life of the secondary battery.
[0031] In any embodiment of the present application, the powder compaction density of the first graphite material under a pressure of 49000N is less than or equal to 1.85g / cm 3 , optional 1.78g / cm 3 -1.85g / cm 3 .
[0032] The first graphite material has a high powder compaction density, which helps to increase the compaction density of the pole piece and improve the energy density of the secondary battery.
[0033] In any embodiment of the present application, the volume distribution particle size Dv50 of the graphite material is recorded as A, and the volume distribution particle size Dv50 of the graphite material after cold pressing under a pressure of 20000N is recorded as B, then the graphite material satisfies: B / A≥85%, which can be optionally 85%-98%.
[0034] In any embodiment of the present application, the amount of primary particles in the first graphite material accounts for 40% to 60%; optionally 50% to 60%.
[0035] In any embodiment of the present application, the graphitization degree of the first graphite material is 88%-95%.
[0036] In any embodiment of the present application, the volume distribution particle size Dv50 of the second graphite material is less than or equal to 15.0 μm, and can be optionally 9.0 μm-14.0 μm.
[0037] The second graphite material has a small volume distribution particle size Dv50, and the path for active ion embedding and extraction is short, which can enhance the transmission performance of active ions and electrons and improve the kinetic performance of the battery.
[0038] In any embodiment of the present application, the tap density of the second graphite material is 1.0 g / cm 3 -1.3g / cm 3 .
[0039] The second graphite material with a tap density within the above range can further enhance the electron conduction between particles and improve the kinetic performance of the battery.
[0040] In any embodiment of the present application, the specific surface area of the second graphite material is 0.75 m 2 / g-1.75m 2 / g.
[0041] The second graphite material with a specific surface area within a suitable range has suitable adsorption sites, which can promote the adsorption of active ions, thereby further improving the kinetic performance of the secondary battery, while reducing the probability of side reactions with the electrolyte, taking into account both the cycle performance and kinetic performance of the battery.
[0042] In any embodiment of the present application, the number of primary particles in the second graphite material accounts for greater than or equal to 80%.
[0043] The primary particles have excellent structural stability, which helps to reduce the breakage of graphite material particles caused by expansion and contraction of the second graphite material during the cycle, improve the stability of the second graphite material, reduce the irreversible consumption of active ions, and achieve improved cycle performance of the secondary battery.
[0044] In any embodiment of the present application, the graphitization degree of the second graphite material is 85%-90%.
[0045] The second graphite material with a graphitization degree within the above range can take into account the material's cycle stability, gram capacity and active ion transport performance, which is conducive to obtaining a battery with high energy density, long cycle and high kinetic performance.
[0046] In any embodiment of the present application, the particle size distribution of the second graphite material (Dv90-Dv10) / Dv50 is 1.20-1.70.
[0047] The second graphite material with a volume particle size distribution within a suitable range is beneficial for making the negative electrode film layer have a suitable pore structure, thereby reducing the difficulty of ion liquid phase transmission and improving the kinetic performance of the secondary battery; in addition, the second graphite material can also have good stacking properties, which is beneficial for improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery.
[0048] In any embodiment of the present application, the gram capacity of the second graphite material is 325 mAh / g-340 mAh / g.
[0049] The second graphite material with a gram capacity within the above range has a relatively small lattice expansion rate and a high crystal structure stability, which can reduce the cycle expansion and full charge expansion of the battery and further improve the cycle stability of the secondary battery.
[0050] A second aspect of the present application provides an electrical device, comprising the secondary battery of the first aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0052] Figure 1 It is a schematic diagram of one embodiment of the negative electrode plate of the present application.
[0053] Figure 2 It is a schematic diagram of another embodiment of the negative electrode plate of the present application.
[0054] Figure 3 It is a schematic diagram of another embodiment of the negative electrode plate of the present application.
[0055] Figure 4 is a schematic diagram of a cross-sectional image of a particle of the first graphite material of the present application.
[0056] Figure 5 It is a schematic diagram of one embodiment of the secondary battery of the present application.
[0057] Figure 6 It is an exploded schematic diagram of one embodiment of the secondary battery of the present application.
[0058] Figure 7 It is a schematic diagram of an embodiment of a battery module of the present application.
[0059] Figure 8 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0060] Fig. 9 yes Figure 8 An exploded schematic diagram of an embodiment of a battery pack is shown.
[0061] Fig.10 It is a schematic diagram of one embodiment of an electric device including the secondary battery of the present application as a power source.
[0062] Fig.11 It is a Raman surface scan image of the first region of one embodiment of the pole piece of the present application.
[0063] Fig.12 This is a Raman surface scan of the second region of one embodiment of the pole piece of the present application.
[0064] In the accompanying drawings, the drawings may not be drawn according to the actual scale. The accompanying drawings are described as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 secondary battery, 51 shell, 52 electrode assembly, 53 cover plate, 10 negative electrode sheet, 101 negative electrode current collector, 102 negative electrode film layer, 102a first surface, 102b second surface, 1021 first region, 1022 second region, 1023 middle region, 200 first graphite material, 201 surface region, 202 internal region. DETAILED DESCRIPTION
[0065] Hereinafter, the embodiments of the secondary battery and the electric device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0066] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0067] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0068] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0069] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0070] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0071] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0072] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.
[0073] If not otherwise specified, the values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.
[0074] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.
[0075] In the present application, the terms "plurality" and "multiple" refer to two or more.
[0076] The capacity and electrochemical performance of negative electrode active materials are often related to their surface disorder. Negative electrode active materials with low surface disorder usually have higher capacity and compactness, which makes the battery have high energy density; but due to its low surface disorder, the crystal interlayer spacing is small, the lattice expansion rate of the negative electrode active material is large during the cycle, the battery cycle life is reduced, and the active ions in the electrolyte are not easy to insert, and the secondary battery kinetic performance is poor.
[0077] Based on this, the present application provides a secondary battery, including a negative electrode sheet, Figures 1 to 3 Schematic diagram of the negative electrode sheet of the present application. Figures 1 to 3 As shown, the negative electrode sheet 10 includes a negative electrode current collector 101 and a negative electrode film layer 102 formed on at least one surface of the negative electrode current collector 101, the negative electrode film layer 102 has a first surface 102a away from the negative electrode current collector 101 and a second surface 102b arranged opposite to the first surface 102a, the thickness of the negative electrode film layer 102 is recorded as H, the area within the thickness range from the second surface 102b of the negative electrode film layer to 0.3H is recorded as the first area 1021 of the negative electrode film layer, the area within the thickness range from the first surface 102a of the negative electrode film layer to 0.3H is recorded as the second area 1022 of the negative electrode film layer, and the active material I in the second area 1022 is D / I G Greater than the I of the active material in the first region 1021 D / I G , ID / I G is the ratio of the D peak intensity to the G peak intensity of the Raman spectrum, I D Indicates that the Raman spectrum is at 1350±100cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±100cm -1 The G peak intensity at . The thickness H of the negative electrode film layer refers to the thickness of the negative electrode film layer located on one side of the negative electrode current collector.
[0078] I in Raman spectra of different regions D / I G Any known method in the art can be used for testing. In the present invention, the LabRAM HR Evolution laser micro-Raman spectrometer is used for testing with reference to GB / T 40219-2021. A solid laser with a wavelength of 523 nm is used as the light source, the beam diameter is 1.2 μm, the power is 1 mW, 100 points are collected in an area of 100 μm×100 μm, and the relative humidity of each point at 1350±100 cm is calculated. -1 The peak intensity I D and 1580±100cm -1 The peak intensity I G I D / I G The ratio of 100 points D / I G The median value is taken as the I D / I G . Fig.11 is a Raman surface scan of a first region of an embodiment of a pole piece of the present application; Fig.12 : is a Raman surface scan of the second region of an embodiment of the pole piece of the present application. As can be seen from the figure, in some embodiments, the active material in the second region has a higher I D / I G And the distribution range is wider.
[0079] In some embodiments, the I of the active material in the second region D / I G Greater than the I of the active material in the first region D / I G In the present application, the thickness of the negative electrode film layer can be tested by a method known in the art. As an example, a micrometer (such as Mitutoyo 293-100, with an accuracy of 0.1 μm) is used for measurement.
[0080] Raman spectroscopy I D / I GIt can be used to characterize the disorder degree of the surface of the active material. It can be understood that the first region and the second region each include at least one active material. D / I G Greater than the I of the active material in the first region 1021 D / I G This does not mean that the active material I in the second region 1022 D / I G is greater than the I of any active material in the first region 1021 D / I G The I of the active material in the second region 1022 of the negative electrode sheet located away from the current collector D / I G Greater than the I of the active material in the first region 1021 D / I G , which means that the active material in the second region outside the electrode has a higher average disorder degree than the active material in the first region. In materials with high disorder, active ions are more easily embedded in and extracted from the active material, which can effectively reduce the volume expansion during ion extraction and improve the battery's cycle performance; at the same time, the electrolyte is also more likely to infiltrate the active material, thereby improving the battery's kinetic performance. The I of the active material in the first region 1021 of the negative electrode near the current collector D / I G The lower the active material, the higher the capacity and the easier it is to be compacted during the cold pressing process, thus improving the compaction of the pole piece and achieving a high energy density of the secondary battery. D / I G The single-layer pole piece made of mixed active materials can achieve the same battery energy density at a lower negative electrode film thickness through a double-layer design, further overcoming the problem of too long transmission path and reduced battery dynamics caused by high negative electrode film thickness. Therefore, the secondary battery can improve the battery's cycle stability and dynamic performance while taking into account the battery's energy density.
[0081] In some embodiments, the active material in the second region has an I D / I G The active material I in the first region D / I G The difference ΔK satisfies: 0<ΔK≤0.4, and can be selected as 0.1≤ΔK≤0.25.
[0082] In some embodiments, the active material in the second region has an I D / I G The active material I in the first region D / I GThe difference ΔK is 0.01, 0.03, 0.06, 0.09, 0.12, 0.15, 0.18, 0.20, 0.23, 0.25, 0.30, 0.35, 0.40 or any range therebetween.
[0083] I of the active material in the second region D / I G I of the active material in the first region D / I G The secondary battery with the difference ΔK within the above range can more effectively take into account the cycle stability, dynamic performance and battery capacity of the battery.
[0084] In some embodiments, the active material in the first region has D / I G Less than or equal to 0.14, optionally 0.05-0.1; and / or, I of the active material in the second region D / I G Greater than or equal to 0.1, optional range is 0.2-0.35.
[0085] In some embodiments, the active material in the first region has D / I G The options are 0.01, 0.03, 0.06, 0.09, 0.1, 0.14 or any range therebetween.
[0086] In some embodiments, the active material in the second region has an I D / I G The options include 0.1, 0.13, 0.16, 0.19, 0.22, 0.25, 0.35 or any range therebetween.
[0087] I of the active material in the first region D / I G I of the active material in the second region D / I G In the appropriate range, secondary batteries can better improve the battery's cycle stability and kinetic performance.
[0088] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the active material in the second region is greater than the particle size distribution (Dv90-Dv10) / Dv50 of the active material in the first region.
[0089] In this article, the terms "Dv90" and "Dv10" refer to the particle sizes corresponding to when the cumulative volume distribution number of particles reaches 90% and 10% in the particle size distribution curve, respectively.
[0090] In the present application, the volume distribution particle size Dv90 and Dv10 of the material can be tested by methods known in the art. As an example, referring to GB / T 19077-2016, a laser particle size analyzer is used for determination. The testing instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0091] The active material in the second region 1022 of the negative electrode sheet away from the current collector has a larger particle size distribution, which is beneficial to the infiltration of the electrolyte in the negative electrode sheet and improves the kinetic performance; while the active material in the first region 1021 close to the current collector has a smaller particle size distribution, which is beneficial to obtaining tightly packed negative electrode active materials and improving the compaction density of the negative electrode sheet. In other words, the negative electrode sheet requires a smaller cold pressing pressure to achieve the same compaction density, thereby reducing the probability of cracking of the active material during the cold pressing process, further improving the integrity of the active material during the processing process, and improving the cycle stability of the battery.
[0092] In some embodiments, the degree of graphitization of the active material in the second region is less than the degree of graphitization of the active material in the first region.
[0093] As used herein, the term "degree of graphitization" refers to an index measuring the degree to which carbon atoms form a close-packed hexagonal graphite crystal structure.
[0094] In the present application, the degree of graphitization of the active material can be tested by methods known in the art. As an example, an X-ray diffractometer (such as Bruker D8 Discover) is used for testing, and JIS K0131-1996 and JB / T4220-2011 are referred to to obtain the average interlayer spacing d002 of the (002) crystal plane in the crystal structure of the graphite material, and then the degree of graphitization is calculated according to the formula g=(0.344-d002) / (0.344-0.3354)×100%. In the above formula, d002 is the average interlayer spacing of the (002) crystal plane in the crystal structure of the graphite material expressed in nanometers (nm).
[0095] Active materials with low graphitization degree often have larger interlayer spacing, which is conducive to the deintercalation of active ions. The active materials located in the second region of the negative electrode sheet away from the current collector have low graphitization degree, which is beneficial to improving the battery kinetic performance while reducing the volume expansion of the electrode sheet caused by the deintercalation of active ions, and comprehensively improving the cycle stability of the battery.
[0096] In some embodiments, the number ratio of primary particles of the active material in the second region is higher than the number ratio of primary particles of the active material in the first region.
[0097] As used herein, the term "primary particles" refers to initial particles formed during the processing of graphite raw materials, and the primary particles are non-agglomerated particles.
[0098] In the present application, the percentage of primary particles in the active material can be tested by methods known in the art. As an example, a cross-section polisher (such as the IB-09010CP argon ion cross-section polisher of Japan's JEOL company) can be used to prepare the cross section of the negative electrode plate; then, referring to JY / T010-1996, a scanning electron microscope (such as the Sigma 300 scanning electron microscope of Germany's ZEISS company) is used to scan the cross section of the negative electrode plate, and multiple test areas are randomly selected in the test sample. Images of the multiple test areas are obtained using a scanning electron microscope, and the ratio of the number of active materials with primary particle morphology in each image to the total number of active material particles is counted. The average value of the multiple statistical results is the percentage of the number of primary particles in the active material.
[0099] A higher primary particle content in the second region located on the negative electrode plate away from the current collector side is beneficial to improving the particle integrity of the plate during the cold pressing process, reducing the generation of new interfaces, reducing the consumption of active lithium during the cycle process, and further improving the cycle stability of the secondary battery.
[0100] In some embodiments, the active material in the first region includes a first graphite material, and a first particle body of the first graphite material includes an internal region and a surface region at least partially surrounding the internal region, wherein the surface region refers to a region extending 30 nm from the surface of the first particle body of the first graphite material to the interior of the particle, and the surface region includes a disordered layer.
[0101] Figure 4 is a schematic diagram of a cross-sectional image of a particle of the first graphite material 200 of the present application. Figure 4 As shown, the region extending 30 nm inward from the surface of the first particle body of the first graphite material 200 is the surface region 201, the region inside the surface region 201 is the internal region 202, and the surface region 201 includes a disordered layer.
[0102] The carbon material in the disordered layer can be characterized by transmission electron microscopy (TEM) testing. By cutting a thin slice of about 100nm thickness from the middle of the graphite material particle body using a focused ion beam (FIB), and then performing a TEM test on the slice, it can be observed that the surface area includes lattice fringes showing long-range disorder and short-range order disordered layers, and the electron diffraction pattern at the disordered layer is halo-shaped.
[0103] In some embodiments, the disordered layer has a thickness of 1 nm to 20 nm.
[0104] In the present application, the thickness of the disordered layer can be tested by methods known in the art, and as an example, can be obtained by transmission electron microscopy (TEM) testing. A thin slice of about 100 nm thickness is cut from the middle of the graphite material particle body by a focused ion beam (FIB), and then the thin slice is subjected to TEM testing to obtain the original TEM test image, and the original image format (xx.dm3) is saved. The original image obtained by the above TEM test is opened in Digital Micrograph software, and the disordered layer is identified by lattice spacing, angle information and diffraction pattern.
[0105] In some embodiments, the thickness of the disordered layer is 1 nm, 4 nm, 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 16 nm, 20 nm, or any range therebetween.
[0106] Different from the active material with disordered layer coated on the surface of the graphite particle body, the disordered layer of the first graphite material is a part of the graphite particle body, that is, the disordered layer structure in the surface region of the first graphite material and the other parts of the first graphite material are derived from the same precursor, which makes the disordered layer of the first graphite material have high uniformity and extremely thin thickness. The first graphite material has a disordered layer on the surface and has a low I D / I G .
[0107] The disordered layer mainly includes amorphous carbon. The carbon atoms in the amorphous carbon structure have no regular arrangement, which makes the interaction between its molecules more complicated, resulting in higher strength and hardness than the graphite crystals in the internal area, which reduces the probability of surface damage of graphite particles due to friction between particles and between particles and stirring tanks during slurry preparation, reduces the risk of cracking of negative electrode active material particles and exposing new interfaces during the cold pressing of the pole piece, and keeps the graphite material in a higher degree of integrity during the manufacturing process. Graphite materials with high particle integrity have fewer surface defects and a good interface with the electrolyte, which can effectively reduce the side reactions between the negative electrode and the electrolyte, reduce the loss of active lithium, and improve the cycle stability of the battery. At the same time, the first graphite material will not sacrifice the capacity of the graphite material and the energy density of the battery because of the excessive disorder of its surface layer, and can take into account the energy density of the battery while improving the cycle stability of the battery.
[0108] In some embodiments, the active material in the second region includes a second graphite material, the second graphite material includes a second particle body and a coating layer at least partially coating the surface of the second particle body, and the coating layer includes amorphous carbon.
[0109] In this article, the term "amorphous carbon" refers to a non-crystalline structure composed of carbon elements, whose hybridization is sp3 With sp 2 The hybrid mixed structure makes it different from the crystalline carbon of the crystalline system, and has a structure and properties similar to amorphous objects (such as glass).
[0110] The amorphous carbon herein can be formed by carbonizing an organic carbon source. The organic carbon source can be a carbonaceous material suitable for coating known in the art, for example, one or more of coal tar, petroleum tar, phenolic resin, coconut shell, etc.
[0111] In the present application, the morphology of the second graphite material can be characterized by transmission electron microscopy.
[0112] The coating layer on the surface of the second graphite material can greatly increase the surface disorder of the active material in the second region. The highly disordered surface of the second graphite material makes it easier for active ions to be deintercalated and reduces the volume expansion during the deintercalation of active ions, further improving the dynamic performance of the battery.
[0113] In some embodiments, the powder compaction density of the second graphite material under a pressure of 49000N is 1.60g / cm 3 -1.80g / cm 3 .
[0114] In some embodiments, the powder compaction density of the second graphite material under a pressure of 49000N is 1.60g / cm 3 , 1.65g / cm 3 , 1.70g / cm 3 , 1.75g / cm 3 , 1.80g / cm 3 Or any range of values in between.
[0115] In this article, the term "powder compaction density" refers to the density of the powder to be tested under a preset pressure. The greater the powder compaction density, the higher the mass of the powder material per unit volume. For graphite materials, the higher the powder compaction density, the greater the compaction density of the negative electrode film layer, which is more conducive to improving the energy density of the secondary battery.
[0116] The method for measuring the compacted density of the powder can be any method known in the art. For example, referring to GB / T24533-2009, 1g of graphite material powder is weighed and added to a bottom area of 1.327cm 2 The mold is pressurized to a specific pressure, such as 49000N, and the pressure is maintained for 30s, then the pressure is released and maintained for 10s. The powder compaction density of the graphite material under the selected pressure is measured by an electronic pressure testing machine (such as UTM7305 electronic pressure testing machine).
[0117] Graphite materials with large surface disorder often have high surface strength and hardness, so they are difficult to compact under pressure and have low powder compaction density. The second graphite material has a high surface disorder while still maintaining a high powder compaction density, which is conducive to increasing the ultimate compaction density of the pole piece, thereby further improving the energy density of the battery.
[0118] In some embodiments, the specific surface area of the first graphite material is 1.0 m 2 / g-1.8m 2 / g, optional 1.1m 2 / g-1.7m 2 / g.
[0119] In the present application, the specific surface area of the active material can be tested by methods known in the art. As an example, referring to GB / T 19587-2017, the specific surface area analysis test method of nitrogen adsorption is used for testing, and the specific surface area is calculated by the BET (BrunauerEmmett Teller) method. The testing instrument can be the Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.
[0120] In some embodiments, the specific surface area of the first graphite material is 1.0 m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g or any range of values between them.
[0121] The low specific surface area of the first graphite material helps to further reduce the degree of side reactions of the active material and improve the cycle life of the secondary battery.
[0122] In some embodiments, the volume distribution particle size Dv50 of the first graphite material is 7.0 μm-14.0 μm, and can be optionally 8.0 μm-12.0 μm.
[0123] In some embodiments, the volume distribution particle size Dv50 of the first graphite material is 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, or any range therebetween.
[0124] In some embodiments, the particle size distribution of the first graphite material (Dv90-Dv10) / Dv50 is 1.0-1.4, and can be optionally 1.1-1.3.
[0125] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first graphite material is 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3 or any range therebetween.
[0126] Controlling the particle size distribution of the first graphite material within the above range is conducive to obtaining tightly packed negative electrode active materials and improving the compaction density of the negative electrode sheet. In other words, the cold pressing pressure required for the negative electrode sheet to achieve the same compaction density is smaller, thereby reducing the probability of cracking of the active material during the cold pressing process, and further improving the integrity of the active material during the processing process; and the small stress inside the first graphite material particles is conducive to maintaining the long-period pore structure of the electrode sheet during the cycle, and the original pore structure of the electrode sheet can be maintained during the cycle, so that the lithium ion lithium insertion path remains unobstructed, while reducing the re-filming of the negative electrode active material during the charging process, improving the dynamic performance and cycle life. Furthermore, the particle size distribution within the above range can also improve the uniformity of lithium insertion between particles, reduce polarization, avoid lithium precipitation caused by uneven current density, and is conducive to achieving long-term cycle stability. In addition, the particle size distribution within the above range is also helpful to improve the processing performance of the electrode sheet, and will not affect the uniformity of slurry stirring due to too many small-sized particles in the first graphite material, which is conducive to improving the uniformity and stability of the quality of the electrode sheet, and helps to achieve long-term cycle stability.
[0127] In some embodiments, the gram capacity of the first graphite material is 345 mAh / g-355 mAh / g, and can be optionally 347 mAh / g-353 mAh / g.
[0128] As used herein, the term "gram capacity" refers to the ratio of the amount of electricity that an active material can release to the mass of the active material.
[0129] In this application, the gram capacity of the graphite material can be tested by methods known in the art. As an example, the graphite material sample is fully stirred and mixed with the conductive agent carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 91.6:1.8:6.6 in an appropriate amount of solvent NMP to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet is used as the counter electrode, the polypropylene (PP) film is used as the isolation membrane, and the electrolyte is injected, wherein the electrolyte formula used is as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. Assembled into a CR2430 button cell in an argon-protected glove box. At 25°C, the button cell prepared above was first discharged at a constant current of 0.05C to 0.005V, then discharged at a constant current of 10μA to 0.005V, and left to stand for 5 minutes, and the first cycle discharge capacity of the button cell was recorded; then, the button cell was charged at a constant current of 0.1C to 2.0V, and the charging capacity of the button cell was recorded. The ratio of the charging capacity of the button cell to the mass of the graphite material sample is the gram capacity of the graphite material.
[0130] In some embodiments, the gram capacity of the first graphite material is 345 mAh / g, 346 mAh / g, 347 mAh / g, 348 mAh / g, 349 mAh / g, 350 mAh / g, 351 mAh / g, 352 mAh / g, 353 mAh / g, 354 mAh / g, 355 mAh / g, or any range therebetween.
[0131] The first graphite material with a gram capacity within the above range will not undergo significant lattice expansion during the charge and discharge process due to its high graphitization degree; nor will it be difficult to compact the material due to its low graphitization degree. In order to achieve the same electrode compaction density, a higher cold pressing pressure is required, which will cause cracks during the cold pressing process and generate new interfaces during the cycle process to consume too much active lithium. The above two aspects can comprehensively improve the cycle life of the secondary battery.
[0132] In some embodiments, the powder compaction density of the first graphite material under a pressure of 49000N is less than or equal to 1.85g / cm 3 , optional 1.78g / cm 3 -1.85g / cm 3 .
[0133] The first graphite material has a high powder compaction density, which helps to increase the compaction density of the pole piece and improve the energy density of the secondary battery.
[0134] In some embodiments, the volume distribution particle size Dv50 of the graphite material is recorded as A, and the volume distribution particle size Dv50 of the graphite material after cold pressing under a pressure of 20000N is recorded as B, then the graphite material satisfies: B / A≥85%, which can be optionally 85%-98%.
[0135] In this article, "cold pressing" refers to a pressure processing method performed at room temperature. The Dv50 ratio of the powder before and after cold pressing can be calculated by the ratio of the Dv50 of the powder and the Dv50 measured by scraping the powder after cold pressing the electrode.
[0136] In some embodiments, A / B can be selected as 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100% or any range therebetween.
[0137] In some embodiments, the amount of primary particles in the first graphite material accounts for 40% to 60%, and can be optionally 50% to 60%.
[0138] In some embodiments, the amount of primary particles in the first graphite material accounts for 40%, 45%, 50%, 55%, 60% or any range therebetween.
[0139] In some embodiments, the first graphite material has a degree of graphitization of 88% to 95%.
[0140] In some embodiments, the degree of graphitization of the first graphite material is 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, or any range therebetween.
[0141] In some embodiments, the first graphite material I D / I G is 0.05-0.1, among which I D Indicates that the Raman spectrum is at 1350±100cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±100cm -1 The G peak intensity at .
[0142] In some embodiments, the first graphite material I D / I G It is 0.05, 0.06, 0.09, 0.1 or any numerical range therebetween.
[0143] In some embodiments, the volume distribution particle size Dv50 of the second graphite material is less than or equal to 15.0 μm, and can be optionally 9.0 μm-14.0 μm.
[0144] In some embodiments, the volume distribution particle size Dv50 of the second graphite material is 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm or any range therebetween.
[0145] The second graphite material has a small volume distribution particle size Dv50, and the path for active ion embedding and extraction is short, which can enhance the transmission performance of active ions and electrons and improve the kinetic performance of the battery.
[0146] In some embodiments, the tap density of the second graphite material is 1.0 g / cm 3 -1.3g / cm 3 .
[0147] As used herein, the term "tapped density" refers to the mass per unit volume of powder in a container measured after being tapped under specified conditions.
[0148] In the present application, the tap density of the active material can be tested by a method known in the art. As an example, it can be measured by using a powder tap density tester in accordance with GB / T 5162-2006. The test instrument can be Dandong Better BT-301, and the test parameters are as follows: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, vibration number 5000 times, and measuring cylinder 25mL.
[0149] In some embodiments, the tap density of the second graphite material is 1.0 g / cm 3 , 1.05g / cm 3 , 1.2g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 Or any range of values in between.
[0150] The second graphite material with a tap density within the above range can further enhance the electron conduction between particles and improve the kinetic performance of the battery.
[0151] In some embodiments, the specific surface area of the second graphite material is 0.75 m 2 / g-1.75m 2 / g.
[0152] In some embodiments, the specific surface area of the second graphite material is 0.75 m 2 / g, 0.85m 2 / g, 0.95m 2 / g, 1.05m 2 / g, 1.15m2 / g, 1.25m 2 / g, 1.35m 2 / g, 1.45m 2 / g, 1.55m 2 / g, 1.65m 2 / g, 1.75m 2 / g or any range of values between them.
[0153] The second graphite material with a specific surface area within a suitable range has suitable adsorption sites, which can promote the adsorption of active ions, thereby further improving the kinetic performance of the secondary battery, while reducing the probability of side reactions with the electrolyte, taking into account both the cycle performance and kinetic performance of the battery.
[0154] In some embodiments, the number of primary particles in the second graphite material accounts for greater than or equal to 80%.
[0155] In some embodiments, the amount of primary particles in the second graphite material accounts for 80%, 84%, 88%, 92%, 96%, 100% or any range therebetween.
[0156] The primary particles have excellent structural stability, which helps to reduce the breakage of graphite material particles caused by expansion and contraction of the second graphite material during the cycle, improve the stability of the second graphite material, reduce the irreversible consumption of active ions, and achieve improved cycle performance of the secondary battery.
[0157] In some embodiments, the second graphite material has a degree of graphitization of 85%-90%.
[0158] In some embodiments, the degree of graphitization of the second graphite material is 85%, 86%, 87%, 88%, 89%, 90%, or any range therebetween.
[0159] The second graphite material with a graphitization degree within the above range can take into account the material's cycle stability, gram capacity and active ion transport performance, which is conducive to obtaining a battery with high energy density, long cycle and high kinetic performance.
[0160] In some embodiments, the particle size distribution of the second graphite material (Dv90-Dv10) / Dv50 is 1.20-1.70.
[0161] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the second graphite material is 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.65, 1.70 or any range therebetween.
[0162] The second graphite material with a volume particle size distribution within a suitable range is beneficial for making the negative electrode film layer have a suitable pore structure, thereby reducing the difficulty of ion liquid phase transmission and improving the kinetic performance of the secondary battery; in addition, the second graphite material can also have good stacking properties, which is beneficial for improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery.
[0163] In some embodiments, the second graphite material I D / I G is 0.1-0.35, among which I D Indicates that the Raman spectrum is at 1350±100cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±100cm -1 The G peak intensity at .
[0164] In some embodiments, the second graphite material I D / I G It is 0.1, 0.12, 0.15, 0.18, 0.21, 0.23, 0.25, 0.30, 0.35 or any numerical range therebetween.
[0165] In some embodiments, the second graphite material has a gram capacity of 325 mAh / g to 340 mAh / g.
[0166] The second graphite material with a gram capacity within the above range has a relatively small lattice expansion rate and a high crystal structure stability, which can reduce the cycle expansion and full charge expansion of the battery and further improve the cycle stability of the secondary battery.
[0167] In some embodiments, the first graphite material is prepared by the following method: providing a first raw material; processing the first raw material to obtain a first intermediate product; performing a first graphitization treatment on the first intermediate product to obtain the first graphite material.
[0168] Herein, the term "graphitization treatment" refers to the heat treatment process of carbon materials, which is the process in which the carbon materials transform from a two-dimensional carbon network structure to a three-dimensional ordered structure through "microcrystal" growth under high temperature.
[0169] In some embodiments, the maximum power of the first graphitization process is 70%-90% of the rated power of the first graphitization process equipment.
[0170] In some embodiments, the power of the first graphitization process may be 70%, 75%, 80%, 85%, 90% of the rated power of the first graphitization process equipment, or any range of values therebetween.
[0171] It can be understood that graphitization equipment refers to any device capable of graphitization, including but not limited to Acheson furnace, box furnace, inner series furnace, continuous graphitization, electric calcining furnace, medium frequency furnace, tubular furnace, etc. The rated power of graphitization equipment produced by different manufacturers may be different, and you can choose according to the actual situation.
[0172] The first graphitization treatment power used in this application needs to be lower than the rated power of the first graphitization treatment equipment to achieve uniformity of the temperature field during the graphitization treatment process, ensure the consistency of the material's gram capacity, and help improve the cycle life of the battery.
[0173] In some embodiments, the first graphitization treatment equipment is an inner series furnace, and the rated power of the inner series furnace is 25000-32000W.
[0174] In some embodiments, the first graphitization treatment equipment is an Acheson furnace, and the rated power of the Acheson furnace is 28000-30000W.
[0175] In some embodiments, the maximum power of the first graphitization process is 22000W-25000W.
[0176] In some embodiments, the maximum power of the first graphitization process may be 22000 W, 22500 W, 23000 W, 23500 W, 24000 W, 25000 W, or any range therebetween.
[0177] By controlling the maximum power of the first graphitization treatment, the degree of graphitization of the graphite material during the heat treatment process can be effectively controlled. While the internal region of the particles of the first graphite material is highly graphitized, a uniform disordered layer is formed in the surface region, which is beneficial to improving the cycle stability of the secondary battery.
[0178] In some embodiments, the constant power time of the first graphitization treatment at maximum power is 10 h to 50 h.
[0179] In some embodiments, the constant power time of the first graphitization treatment at maximum power is 10 h, 13 h, 16 h, 19 h, 22 h, 25 h, 28 h, 31 h, 33 h, 36 h, 39 h, 42 h, 45 h, 48 h, 50 h, or any range therebetween.
[0180] In some embodiments, the temperature of the first graphitization treatment is 2600°C to 3000°C.
[0181] In some embodiments, the temperature of the first graphitization treatment is 2600° C., 2700° C., 2800° C., 2900° C., 3000° C., or any range therebetween.
[0182] The appropriate graphitization treatment temperature and the appropriate graphitization treatment time are not likely to cause excessive rearrangement of the precursor, resulting in a high specific surface area of the graphite material after graphitization and deterioration of high-temperature performance; and can effectively increase the graphitization degree of the first graphite material, thereby facilitating the improvement of the cycle life of the secondary battery.
[0183] In some embodiments, the first raw material includes at least one of petroleum coke, needle coke, and asphalt coke, and needle coke may be selected.
[0184] As used herein, the term "petroleum coke" refers to coke formed by high-temperature carbonization of petroleum residue or petroleum asphalt.
[0185] As used herein, the term "needle coke" refers to coal tar pitch or petroleum pitch, which, after undergoing liquid phase carbonization to generate an anisotropic mesophase, can generate coke with a needle-like texture after undergoing processes such as high-temperature carbonization.
[0186] As used herein, the term "pitch coke" refers to a solid material produced by carbonizing coal tar pitch at high temperatures.
[0187] Among them, needle coke has a series of advantages such as low thermal expansion coefficient, low porosity, low sulfur, low ash, low metal content, high conductivity and easy graphitization, etc. The graphite material after graphitization can reach a high ultimate compaction density and has a low cyclic expansion rate.
[0188] In some embodiments, based on the total volume of the first raw material structure, the volume proportion of the fiber-type structure in the first raw material is greater than or equal to 55%, and can be optionally 58%-70%.
[0189] In this article, "fibrous structure" is also called streamlined structure, which refers to the structure of the raw material with obvious fibrous texture observed under a microscope.
[0190] According to the morphological characteristics and isochromatic zone size of the coke material under a polarizing microscope, its microstructure can be divided into mosaic type, regional type and fiber type. Usually, the isochromatic zone microstructure with a size less than 30um is judged as mosaic type; the isochromatic zone microstructure with a size greater than 30um is judged as regional type, and the anisotropic strip-shaped isochromatic zone is judged as a fiber type structure.
[0191] In this application, the volume proportion of the fiber structure in the raw material can be tested by methods known in the art. As an example, take the raw material according to GB 1997-89, mix the raw material crushed to 1mm, shrink it to 40g~50g, use a square hole sieve to take 0.07mm~1.0mm grade sample 4g~5g for film making; prepare powder coke and block coke light film according to MT 116.1-86, the diameter of the powder coke light film shall not be less than 22mm, and the volume occupied by the cement shall be less than 1 / 3; place the sample on a slide with glue, flatten it, and then place it on the stage to focus, calibrate the microscope and adjust the polarizer and analyzer to make them orthogonal. Insert the azurite inspection plate (1λ) to make the field of view present the interference color of primary red; determine the step length of the moving ruler to ensure that more than 400 effective measuring points are evenly distributed, and the point spacing is 0.3~0.5mm and the line spacing is generally 0.5~0.8mm. Starting from one end of the sample, determine the type of microstructure under the intersection of the crosshairs, and divide the number of effective measuring points of the fiber-type structure optical organization by the total number of statistical testing points as the volume proportion of the fiber-type structure in the raw material.
[0192] In some embodiments, based on the total volume of the first raw material structure, the volume proportion of the fibrous structure in the first raw material can be selected to be 55%, 58%, 60%, 65%, 70% or any range of values therebetween.
[0193] Raw materials with more fiber-type structures are conducive to improving the compaction density and gram capacity of the first graphite material, so that the first graphite material retains a high degree of integrity during the compaction process, and the battery has a high cycle life and good energy density; but too high a proportion of fiber-type structures will increase the cost and expansion rate of graphite materials and deteriorate dynamic performance. The first raw material with a volume proportion of fiber-type structures within the above range has both low cost and good gram capacity of graphite, and the battery cell has a full life cycle kinetic window, thereby comprehensively improving the long-term cycle life and electrochemical performance of the battery.
[0194] In some embodiments, the maximum gram capacity that can be achieved by the first feedstock is greater than the gram capacity of the graphite material.
[0195] By using high-grade raw materials and controlling the degree of graphitization, the maximum gram capacity that can be achieved by the first raw material will not be fully utilized, and a graphite material including a disordered layer in the surface area is obtained, so as to achieve a balance between battery cycle life and kinetic performance.
[0196] In some embodiments, the processing of raw materials specifically includes: crushing, shaping and grading the raw materials to obtain a first precursor; granulating the first precursor to obtain a first precursor over-finished product; low-temperature carbonizing a mixture of the first precursor and the first precursor over-finished product to obtain the first intermediate product.
[0197] Crushing is the process of reducing the particle size of raw materials. The raw materials can be crushed by any mechanical device such as crusher, mechanical mill, etc.
[0198] Shaping and classification is the process of adjusting the particle size distribution of the raw material to obtain a first precursor that meets the particle size requirements. The particle size and particle size distribution of the first precursor can be controlled by adjusting the classification frequency and air intake volume.
[0199] It can be understood that low-temperature carbonization of the first precursor and the first precursor over-finished product to obtain the intermediate product includes both low-temperature carbonization of a mixture of the first precursor and the first precursor over-finished product to obtain the intermediate product and low-temperature carbonization of the first precursor and the first precursor over-finished product to obtain the first intermediate product and the second intermediate product, respectively.
[0200] In some embodiments, the Dv50 particle size of the first precursor is 6.0 μm to 10.0 μm.
[0201] In some embodiments, the Dv50 particle size of the first precursor is 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, or any range therebetween.
[0202] In some embodiments, the particle size distribution of the first precursor (Dv90-Dv10) / Dv50 is 1.05-1.75.
[0203] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first precursor is 1.05, 1.15, 1.25, 1.35, 1.45, 1.55, 1.65, 1.75 or any range therebetween.
[0204] In some embodiments, the tap density of the first precursor is 0.5 g / cm 3 ~0.7g / cm 3 .
[0205] In some embodiments, the tap density of the first precursor is 0.5 g / cm 3 , 0.55g / cm 3 , 0.6g / cm 3 , 0.65g / cm 3 , 0.7g / cm 3 Or any range of values in between.
[0206] In some embodiments, the Dv50 particle size of the first precursor product is 11.0 μm to 15.0 μm.
[0207] In some embodiments, the Dv50 particle size of the first precursor product is 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm, or any range therebetween.
[0208] The first precursor product is obtained by granulating the first precursor, so the first precursor product mainly forms secondary particles in the graphite material. Controlling the particle size of the first precursor and the first precursor product helps to achieve the regulation of the particle size and particle size distribution of the graphite material and improve the cycle stability of the battery.
[0209] In some embodiments, the crushing, shaping and grading of the raw materials to obtain the first precursor includes: crushing, shaping and grading the raw materials to obtain secondary raw materials; removing fine powder accounting for 10%-35% of the total mass of fine powder in the secondary raw materials to obtain the first precursor; the Dv50 of the fine powder is 3μm-7μm and Dv99 is less than or equal to 30μm, and the particle size distribution of the fine powder (Dv90-Dv10) / Dv50 is greater than 1.6.
[0210] In some embodiments, the second graphite material is prepared by the following method: providing a second raw material; processing the second raw material to obtain a second precursor; performing a second graphitization treatment on the second precursor to obtain a second graphitized product; and performing a surface treatment on the second graphitized product to obtain a second graphite material.
[0211] In some embodiments, surface treating the second graphitized product to obtain the second graphite material includes performing a fusion treatment on the second graphitized product to obtain a second intermediate, and mixing the second intermediate with asphalt to perform a second carbonization treatment to obtain the second graphite material.
[0212] The prior art will directly use asphalt to coat the second graphitized product to increase the disorder of the graphite material surface, thereby improving the dynamic performance of the material. However, directly coating the second graphitized product will seriously affect the powder compaction density of the graphite material, reduce the compaction density of the negative electrode film layer, and thus affect the energy density of the secondary battery. The present application performs a fusion treatment on the second graphitized product before the asphalt coating treatment. The fusion treatment can achieve the purpose of spheroidization and de-edgeing. On the one hand, the second intermediate obtained by fusion spheroidization has a relatively regular structure, which can improve the powder compaction density of the second graphite material. On the other hand, the small particles of graphite produced by de-edgeing can be filled in the gaps of the second intermediate, further improving the powder compaction density of the second intermediate. The fusion treatment can effectively compensate for the adverse effects of the asphalt coating treatment on the powder compaction density of the graphite material, which is conducive to obtaining a negative electrode film layer with a high compaction density, thereby maintaining the high energy density of the battery.
[0213] In some embodiments, the frequency of the fusion process may be selected to be 20 Hz, 25 Hz, 30 Hz, 35 Hz or 40 Hz, or a range between any two of the above values.
[0214] In some embodiments, the fusion treatment time is 5-15 min. In some embodiments, the fusion treatment time can be selected as 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min, or a range between any two of the above values.
[0215] The frequency and time of the fusion treatment affect the powder compaction density and specific surface area of the second graphite material. A high frequency of the fusion treatment can increase the powder compaction density of the second graphite material, while also reducing the damage to the processing equipment caused by an excessively high frequency of the fusion treatment. In addition, a high frequency of the fusion treatment can also increase the specific surface area of the second graphite material and improve the kinetic properties of the material. The time of the fusion treatment affects the powder compaction density, specific surface area and Id / Ig of the second graphite material. A long fusion treatment time can increase the powder compaction density, specific surface area and Id / Ig of the second graphite material, obtain a negative electrode film layer with a high compaction density, and improve the energy density and kinetic properties of the battery.
[0216] In some embodiments, the second carbonization treatment has a treatment temperature of 950-1350°C.
[0217] In some embodiments, the treatment temperature of the second carbonization treatment may be 950° C., 1000° C., 1100° C., 1200° C., 1300° C. or 1350° C., or a range between any two of the above values.
[0218] The treatment temperature of the second carbonization treatment affects the I D / I G If the treatment temperature of the second carbonization treatment is too high, the asphalt coating degree is high, the coating layer integrity of the second graphite material is high, and the I D / I G If the temperature of the second carbonization treatment is too low, the functional groups on the surface of the asphalt may not be completely removed, which may lead to side reactions during the cycle and affect the cycle performance of the battery.
[0219] In some embodiments, the second feedstock comprises one or more of petroleum coke, needle coke, and pitch coke.
[0220] As used herein, the term "petroleum coke" refers to coke formed by high-temperature carbonization of petroleum residue or petroleum asphalt.
[0221] As used herein, the term "needle coke" refers to coal tar pitch or petroleum pitch, which, after undergoing liquid phase carbonization to generate an anisotropic mesophase, can generate coke with a needle-like texture after undergoing processes such as high-temperature carbonization.
[0222] As used herein, the term "pitch coke" refers to a solid material produced by carbonizing coal tar pitch at high temperatures.
[0223] In some embodiments, the second raw material is petroleum coke. Petroleum coke has excellent graphitization performance and low thermal expansion coefficient, which is conducive to obtaining a second graphite material with excellent dynamic performance and cycle stability, and the raw material cost is low, saving costs.
[0224] In some embodiments, based on the total volume of the second raw material structure, the volume proportion of the mosaic structure and the regional structure is greater than or equal to 50%.
[0225] In some embodiments, the volume proportion of the mosaic structure and the regional structure can be selected to be 50%, 60%, 70%, 80%, 90% or 100%, or a range between any two of the above values.
[0226] In some embodiments, processing the second raw material specifically includes the following steps: crushing the second raw material, shaping it, grading it, removing the fine powder after crushing, and obtaining a second precursor, wherein the volume distribution particle size Dv50 of the second precursor is 8.0-16.0 μm, and / or the (Dv90-Dv10) / Dv50 of the second precursor is 1.40-1.70.
[0227] In some embodiments, the volume distribution particle size Dv50 of the second precursor can be selected as 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm or 16.0 μm, or a range between any two of the above values.
[0228] In some embodiments, (Dv90-Dv10) / Dv50 of the second precursor may be 1.40, 1.50, 1.60 or 1.70, or a range between any two of the above values.
[0229] In some embodiments, the maximum power of the second graphitization process is 70%-90% of the rated power of the second graphitization process equipment.
[0230] In some embodiments, the maximum power of the second graphitization process may be selected to be 70%, 75%, 80%, 85%, 90% of the rated power of the second graphitization process equipment, or any range of values therebetween.
[0231] In some embodiments, the maximum power of the equipment in the second graphitization treatment is 21500 W-24000 W. In some embodiments, the maximum power of the equipment in the second graphitization treatment can be selected as 21500 W, 23000 W, 23500 W, 24000 W, or any range therebetween.
[0232] In some embodiments, the constant power time of the second graphitization treatment at the maximum power of the device is 5.5h-7.5h. In some embodiments, the constant power time of the second graphitization treatment at the maximum power of the device can be selected as 5.5h, 6.0h, 6.5h, 7h, 7.5h or any range therebetween.
[0233] The present application has no particular restrictions on the type of secondary battery. For example, the secondary battery can be a lithium-ion battery, etc. In general, a secondary battery includes a positive electrode plate, a negative electrode plate, and an electrolyte, etc. During the charge and discharge process of the secondary battery, active ions are embedded and removed back and forth between the positive electrode plate and the negative electrode plate, and the electrolyte plays a role in conducting active ions between the positive electrode plate and the negative electrode plate. The present application has no particular restrictions on the type of the electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (ie, an electrolyte). Secondary batteries using electrolytes and some secondary batteries using solid electrolytes may also include a separator, which is arranged between the positive electrode plate and the negative electrode plate to play an isolation role.
[0234] [Negative electrode]
[0235] In some embodiments, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0236] like Figures 1 to 3 As shown, the negative electrode film layer 102 further includes a middle region 1023 located between the first region 1021 of the negative electrode film layer and the second region 1022 of the negative electrode film layer and having a thickness of 0.4H (H represents the thickness of the negative electrode film layer 102).
[0237] In some embodiments, the intermediate region includes the first graphite material and / or the second graphite material. Figure 2 As shown, the composition of the middle region 1023 may be the same as that of the first region 1021, whereby the distribution area of the active material in the first region in the thickness direction of the negative electrode film layer 102 is within the thickness range from the second surface 102b of the negative electrode film layer to 0.7H; or Figure 3 As shown, the middle region 1023 may be the same as the second region 1022 in composition, whereby the distribution area of the active material in the second region in the thickness direction of the negative electrode film layer 102 is within the thickness range from the first surface 102a of the negative electrode film layer to 0.7H; or Figure 1 As shown, the middle region 1023 includes both the active material in the first region and the active material in the second region. At this time, the middle region 1023 includes both the layer structure having the active material in the first region and the layer structure having the active material in the second region. The above two layer structures may also have a layer interface.
[0238] In some embodiments, the negative electrode film layer may further include other negative electrode active materials in addition to the above-mentioned active materials. In some embodiments, the other negative electrode active materials include but are not limited to one or more of conventional natural graphite, other artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide and tin alloy material.
[0239] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0240] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0241] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.
[0242] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0243] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the present application also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode collector and the negative electrode film layer and disposed on the surface of the negative electrode collector; in some embodiments, the negative electrode plate described in the present application also includes a protective layer covering the surface of the negative electrode film layer.
[0244] [Positive electrode]
[0245] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0246] The positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0247] The positive electrode film layer generally comprises a positive electrode active material, an optional binder and an optional conductive agent. The positive electrode film layer is generally formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is generally formed by dispersing the positive electrode active material, the optional conductive agent, the optional binder and any other components in a solvent and stirring evenly. The solvent may be N-methylpyrrolidone (NMP), but is not limited thereto. As an example, the binder for the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. As an example, the conductive agent for the positive electrode film layer includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0248] The positive electrode active material may be a positive electrode active material for a secondary battery known in the art.
[0249] When the secondary battery of the present application is a lithium ion battery, the positive electrode active material may include, but is not limited to, one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds. Examples of the lithium transition metal oxide may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds.
[0250] In some embodiments, the positive electrode active material includes a lithium-containing phosphate. Examples of the lithium-containing phosphate may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.
[0251] In the present application, the modified compound of each positive electrode active material mentioned above may be a compound obtained by doping and / or surface coating the positive electrode active material.
[0252] [Electrolytes]
[0253] In some embodiments, the electrolyte is an electrolyte solution, and the electrolyte solution includes an electrolyte salt and a solvent.
[0254] The type of the electrolyte salt is not particularly limited and can be selected according to actual needs.
[0255] When the secondary battery of the present application is a lithium ion battery, as an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0256] The type of the solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent may include ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE) One or more.
[0257] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain properties of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high temperature performance of the secondary battery, and additives that improve the low temperature power performance of the secondary battery.
[0258] [Isolation film]
[0259] The present application has no particular limitation on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.
[0260] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.
[0261] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly by a winding process or a lamination process.
[0262] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0263] In some embodiments, the outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0264] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 5 The secondary battery 5 is a square structure as an example.
[0265] In some embodiments, Figure 6 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are enclosed to form a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.
[0266] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the secondary battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0267] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0268] Figure 7 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 7 As shown, in the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0269] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0270] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0271] Figure 8 and Fig. 9 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 8 and Fig. 9 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0272] Electrical devices
[0273] The present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack of the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0274] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0275] Fig.10 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.
[0276] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0277] Example
[0278] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0279] In the following embodiments and comparative examples, the first carbon-based material can be prepared by the following method of the present application.
[0280] Preparation Example
[0281] Preparation of the First Graphite-A
[0282] The needle coke with a fiber structure of 68% was crushed; the crushed material was shaped to remove fine powder to obtain the first precursor, and the first precursor removed 21% of the mass of fine powder relative to the total mass of fine powder. The fine powder refers to the component with a maximum particle size of less than 5μm. Among them, the Dv50 particle size of the first precursor is 9.0μm, the particle size distribution (Dv90-Dv10) / Dv50 is 1.35, and the tap density of the first precursor is 0.65g / cm 3 .
[0283] Granulate and shape a portion of the first precursor in a reactor to obtain a second precursor process product with a particle size Dv50 of 14.3 um;
[0284] The first precursor and the second precursor process product were placed in a kiln for carbonization at a carbonization temperature of 1100°C and a carbonization time of 24 hours to obtain a first intermediate product and a second intermediate product. The tap density of the first intermediate product was 0.98 g / cm 3 The tap density of the second intermediate product is 0.91 g / cm 3 ;
[0285] The first intermediate product and the second intermediate product are respectively placed in an inner series furnace for graphitization treatment at a temperature of 2800°C. The rated power of the inner series furnace is 28000W, the maximum power of the graphitization treatment is 22400W, and the constant power duration of the maximum power is maintained for 24 hours to obtain primary particles and secondary particles respectively.
[0286] The primary particles and the secondary particles are mixed evenly in a mass ratio of 1:1, and the final graphite material is obtained after sieving.
[0287] The thickness of the disordered layer of the graphite material is 11.2 nm, and the coefficient of variation of the disordered layer thickness is 34.1%. D / IG The interlayer spacing d1 of the disordered layer is 0.3368 nm, the interlayer spacing d2 of the inner region is 0.3361 nm, the particle size distribution (Dv90-Dv10) / Dv50 is 1.28, the B / A value is 93.4%, and the specific surface area is 1.65 m 2 / g, the volume distribution particle size Dv50 is 10.2μm, and the powder compaction density under a pressure of 49000N is 1.81g / cm 3 , the gram capacity is 350.8mAh / g.
[0288] Preparation of the first graphite-B
[0289] The preparation method of the first graphite-B is basically the same as the preparation method of the first graphite-A, except that the temperature of the graphitization treatment is 2850°C, the thickness of the disordered layer of the graphite material is 10.5nm, and I D / I G It is 0.067.
[0290] Preparation of the first graphite-C
[0291] The preparation method of the first graphite-C is basically the same as the preparation method of the first graphite-A, except that the maximum power is the rated power of the equipment and the constant power duration at the maximum power is 36 hours, and the surface area of the prepared graphite material body particles has no disordered layer, I D / I G It is 0.041.
[0292] Preparation of Second Graphite-A
[0293] The petroleum coke raw material with a volume proportion of 68.0% of the mosaic and regional structures is coarsely crushed, and then the coarsely crushed material is crushed and sieved, and the sieved material is shaped and classified, and a certain amount of fine powder is removed during the classification process to obtain precursor particles with a volume distribution particle size Dv50 of 12.0 μm and a particle size distribution (Dv90-Dv10) / Dv50 of 1.61;
[0294] The precursor was placed in a kiln for pre-carbonization at a temperature of 1000°C and a high temperature zone time of 24 hours. The pre-carbonized material was obtained, and its tap density was 0.99 g / cm 3 ;
[0295] The pre-carbonized material is graphitized at a temperature of 2850°C. The graphitization treatment equipment is an inner series furnace with a rated power of 27000W. The maximum power of the graphitization treatment is 23000W. The constant power duration of the maximum power is maintained for 10.0h to obtain a graphitized product.
[0296] The graphitized product is fused in a high-speed fusion machine to obtain an intermediate, the fusion frequency is 30 Hz, the fusion time is 15 min, the intermediate is mixed with asphalt, wherein the mass ratio of the intermediate to asphalt is 98%:2%, and after mixing, it is carbonized at 1150°C for 2 h. After the finished product is demagnetized and mixed batch process, the second graphite-A is obtained.
[0297] Preparation of Second Graphite-B to Second Graphite-D
[0298] The preparation method of the second graphite-B to the second graphite-D is basically the same as the preparation method of the second graphite-A, except that the I of the graphite material is adjusted by adjusting the type of raw materials, the maximum power of the graphitization treatment, the duration of the graphitization treatment or the fusion frequency and fusion time of the fusion treatment. D / I G , please see Table 1 for details.
[0299] Table 1
[0300]
[0301] The performance parameters of graphite materials are shown in Table 2.
[0302] Table 2
[0303]
[0304] Example 1
[0305] The first graphite-A, the conductive agent carbon black (Super P), the thickener sodium carboxymethyl cellulose, and the binder styrene-butadiene rubber were fully stirred and mixed in a proper amount of solvent deionized water at a weight ratio of 96:1:1.8:1.2 to form a first slurry.
[0306] The second graphite-A, the conductive agent carbon black (Super P), the thickener sodium carboxymethyl cellulose, and the binder styrene-butadiene rubber were fully stirred and mixed in a proper amount of solvent deionized water at a weight ratio of 96:1:1.8:1.2 to form a second slurry.
[0307] The first slurry and the second slurry are extruded simultaneously through a double-chamber coating device. The first slurry is coated on the negative electrode current collector copper foil, and the second slurry is coated on the first slurry; after drying and cold pressing, a negative electrode sheet is obtained. The coating mass ratio of the second slurry to the first slurry is 4:6 or 5:5.
[0308] LiFePO4, conductive carbon black and polyvinylidene fluoride were mixed in a weight ratio of 97:1:2, and an appropriate amount of solvent NMP was added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained.
[0309] In an argon atmosphere glove box with a water content of <10ppm, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L, and then vinylene carbonate (VC) is added, and the content of VC is 2% of the total mass of the electrolyte.
[0310] Polypropylene film is used as the isolation film.
[0311] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0312] The negative electrode film layer has a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface. The thickness of the negative electrode film layer H is 140 μm. The area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the first area of the negative electrode film layer, and the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the second area of the negative electrode film layer.
[0313] Embodiment 2-7
[0314] The preparation method is basically the same as that of Example 1, except that the graphite material combination of the upper and lower layers is changed, as shown in Table 3 for details.
[0315] Comparative Example 1
[0316] The preparation method is basically the same as that of Example 1, except that the graphite material combination of the upper and lower layers is changed, as shown in Table 3 for details.
[0317] Table 3
[0318] Serial number The second region of the negative electrode film The first region of the negative electrode film Example 1 Second Graphite-A First Graphite-A Example 2 Second Graphite-B First Graphite-A Example 3 Second Graphite-C First Graphite-A Example 4 Second Graphite-D First Graphite-A Example 5 70wt% second graphite-A+30wt% first graphite-A First Graphite-A Example 6 Second Graphite-C First Graphite-B Example 7 Second Graphite-C First Graphite-C Comparative Example 1 First Graphite-A Second Graphite-C
[0319] Performance Testing
[0320] (1) Cycle performance test of secondary batteries
[0321] At 60°C, the batteries of the above embodiments and comparative examples were charged at a constant current of 1C to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current ≤ 0.05C, and then discharged at a constant current of 1C to a voltage of 2.5V. This was a charge and discharge process, and the discharge capacity C1 of the first cycle was recorded. The charge and discharge cycles were repeated until the battery capacity decayed to 80% of the initial capacity C1, and the test was stopped, and the number of cycle tests was recorded.
[0322] (2) Charging time test
[0323] At 25°C, the secondary battery was charged to 3.65V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage, and after standing for 5 minutes, the secondary battery was discharged to 2.50V at a constant current of 0.33C, and its actual capacity was recorded as C0.
[0324] Then the secondary battery is charged with constant current at 1.0 C0, 1.3 C0, 1.5 C0, 1.8 C0, 2.0 C0, 2.3 C0, 2.5 C0, 3.0 C0, to 3.5 V or 0 V negative electrode cut-off potential (whichever is reached first), and discharged to 2.5 V at 1 C0 after each charging. The negative electrode potential corresponding to charging to 10%, 20%, 30%, ..., 80% SOC (State of Charge) at different charging rates is recorded, and the charging rate-negative electrode potential curve under different SOC states is drawn. After linear fitting, the charging rate corresponding to the negative electrode potential of 0 V under different SOC states is obtained. The charging rate is the charging window under the SOC state, which is recorded as C10% SOC, C20% SOC, etc. %SOC、C30%SOC、C40%SOC、C50%SOC、C60%SOC、C70%SOC、C80%SOC, according to the formula (60 / C10%SOC+60 / C20%SOC+60 / C30%SOC+60 / C40%SOC+60 / C50%SOC+60 / C60%SOC+60 / C70%SOC+60 / C80%SOC)×10%, the charging time T of the secondary battery from 10%SOC to 80%SOC (under the premise that the secondary battery does not precipitate lithium) is calculated in min. The shorter the charging time, the better the fast charging performance of the secondary battery.
[0325] (3) Secondary battery cycle expansion test
[0326] At 45℃, charge to 3.65V at 1.0C (i.e., the current value that completely discharges the theoretical capacity within 1h), let stand for 10min, and then discharge to 2.5V at 1.0C. This is one charge and discharge process; cycle 300 times under this condition. At 25℃, charge the secondary battery after 300 cycles at 1.0C to 3.65V, and continue to charge at constant voltage to 0.05C. Disassemble the secondary battery and record the thickness of the pole piece at this time, L1. The initial thickness of the pole piece before winding is L0, and (L1 / L0-1)*100% is used as the cycle expansion rate of the pole piece after the 300th cycle.
[0327] Test Results
[0328] The test results are shown in Tables 4 and 5. As can be seen from the table, the I D / I G Greater than the I of the active material in the first region D / I G It helps to improve the cycle stability and kinetic performance of the battery. D / I G A value of 0.2-0.35 helps to further improve the kinetic performance of the battery while maintaining a high cycle life.
[0329] Table 4
[0330]
[0331] It can be seen from Table 5 that the I D / I G It is 0.05-0.1, which is beneficial to further reduce the cycle expansion of the battery and improve the later cycle stability of the battery.
[0332] Table 5
[0333]
[0334] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, characterized in that: The invention comprises a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, the negative electrode film layer has a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is recorded as H, the area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the first area of the negative electrode film layer, the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the second area of the negative electrode film layer, and the I of the active material in the second area is D / I G Greater than the I of the active material in the first region D / I G , I D / I G is the ratio of the D peak intensity to the G peak intensity of the Raman spectrum, I D Indicates that the Raman spectrum is at 1350±100cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±100cm -1 The G peak intensity at .
2. The secondary battery according to claim 1, characterized in that: The I of the active material in the second region D / I G The active material I in the first region D / I G The difference ΔK satisfies: 0<ΔK≤0.4, and can be selected as 0.1≤ΔK≤0.
25.
3. The secondary battery according to claim 1 or 2, characterized in that: The I of the active material in the first region D / I G Less than or equal to 0.14, optionally 0.05-0.1; and / or, I of the active material in the second region D / I G Greater than or equal to 0.1, optional range is 0.2-0.
35.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The particle size distribution (Dv90-Dv10) / Dv50 of the active material in the second region is greater than the particle size distribution (Dv90-Dv10) / Dv50 of the active material in the first region.
5. The secondary battery according to any one of claims 1 to 4, characterized in that: The degree of graphitization of the active material in the second region is lower than the degree of graphitization of the active material in the first region.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The number ratio of primary particles of the active material in the second region is higher than the number ratio of primary particles of the active material in the first region.
7. The secondary battery according to any one of claims 1 to 6, characterized in that: The active material in the first region includes a first graphite material, and the first particle body of the first graphite material includes an internal region and a surface region at least partially surrounding the internal region, wherein the surface region refers to a region extending 30 nm from the surface of the first particle body of the first graphite material to the interior of the particle, and the surface region includes a disordered layer.
8. The secondary battery according to claim 7, characterized in that: The thickness of the disordered layer is 1 nm-20 nm.
9. The secondary battery according to any one of claims 1 to 8, characterized in that: The active material in the second region includes a second graphite material, the second graphite material includes a second particle body and a coating layer at least partially coating the surface of the second particle body, and the coating layer includes amorphous carbon.
10. The secondary battery according to claim 9, characterized in that: The powder compaction density of the second graphite material under a pressure of 49000N is 1.60g / cm 3 -1.80g / cm 3 .
11. The secondary battery according to any one of claims 7 to 10, characterized in that: The first graphite material satisfies at least one of the following conditions: (1) The specific surface area of the first graphite material is 1.0 m 2 / g-1.8m 2 / g, optional 1.1m 2 / g-1.7m 2 / g; (2) The volume distribution particle size Dv50 of the first graphite material is 7.0 μm-14.0 μm, and can be optionally 8.0 μm-12.0 μm; (3) The particle size distribution (Dv90-Dv10) / Dv50 of the first graphite material is 1.0-1.4, and can be 1.1-1.3; (4) The gram capacity of the first graphite material is 345 mAh / g-355 mAh / g, and can be optionally 347 mAh / g-353 mAh / g; (5) The powder compaction density of the first graphite material under a pressure of 49000N is less than or equal to 1.85g / cm 3 , optional 1.78g / cm 3 -1.85g / cm 3 ; (6) The volume distribution particle size Dv50 of the graphite material is recorded as A, and the volume distribution particle size Dv50 of the graphite material after cold pressing under a pressure of 20000N is recorded as B. Then the graphite material satisfies: B / A ≥ 85%, which can be 85%-98%; (7) The amount of primary particles in the first graphite material accounts for 40% to 60%; optionally 50% to 60%; (8) The graphitization degree of the first graphite material is 88%-95%.
12. The secondary battery according to any one of claims 9 to 10, characterized in that: The second graphite material satisfies at least one of the following conditions: (1) The volume distribution particle size Dv50 of the second graphite material is less than or equal to 15.0 μm, and can be selected from 9.0 μm to 14.0 μm; (2) The tap density of the second graphite material is 1.0 g / cm 3 -1.3g / cm 3 ; (3) The specific surface area of the second graphite material is 0.75 m 2 / g-1.75m 2 / g; (4) The number of primary particles in the second graphite material accounts for greater than or equal to 80%; (5) The degree of graphitization of the second graphite material is 85%-90%; (6) the particle size distribution of the second graphite material (Dv90-Dv10) / Dv50 is 1.20-1.70; (7) The gram capacity of the second graphite material is 325 mAh / g-340 mAh / g.
13. An electrical device comprising the secondary battery according to any one of claims 1 to 11.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
CN111194501A
Anode for lithium secondary battery and lithium secondary battery including the same
CN113851608A
Composite negative plate and lithium ion battery
CN114156436A
Electrochemical device and electronic device including the same
CN115295755A
Nonaqueous electrolyte secondary battery
JP2010267540A
Cited By
Secondary battery and electric apparatus
EP4800752A1